The best practice for virtual conference / discussion in high technology area - Ling, Daniel (Cranfield University, 2002)
This thesis presents analysis of virtual conference. It describes the virtual AS-IS process model, the user groups and the features that are concerned with virtual conferencing. An analysis of asynchronous Vs synchronous conferencing for a high technology business environment is presented. The identified best practise for virtual conference in high technology area and the resulting best practice checklist for virtual conference management and development are determined.